PENGARUH MODEL PEMBELAJARAN MIND MAPPING TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN SEJARAH DI SMA NEGERI 8 PALEMBANG - Apriana Apriana Apriana; Sri Mulyati (Jurnal Muara Pendidikan, 2020)
The reality on the ground shows that most students often feel bored, lazy, sleepy, and bored with history lessons. Therefore, this study aims to determine the Effect of Mind Mapping Learning Model on Student Learning Outcomes in Historical Subjects at SMA Negeri 8 Palembang ". The method used in this research is quantitative research. Based on the results of research and analysis of data output "Test Statistics" known Asymp.Sig. (2-tailed) worth 0,000. Because the value of 0,000 <0.05, it can be concluded that "Ha is accepted". This means that there is a difference between pretest and posttest learning outcomes, so it can be concluded also that "There is an Effect of Mind Mapping Learning Models on Student Learning Outcomes in Historical Subjects at SMA Negeri 8 Palembang".